A educação superior em tempos de pandemia: uma análise da implementação do ensino remoto emergencial na Unitins - Moreira, Daiany Alves Araújo (Universidade Federal do Tocantins, 2022)
Faced with the crisis caused by the COVID -19 pandemic, in which higher education institutions had to paralyze the offer of face -to-face courses, the present research sought to analyze how the process of implementing emergency remote teaching at UNITINS took place, within the scope of the pandemic. of COVID -19. A qualitative approach was used, the data triangulation method and, as data collection instruments, bibliographic and documentary research and a structured (written) interview were used. The implement ation of emergency remote teaching (ERE) at UNITINS took place as an “action in experiment” due to the pandemic context. The main challenges related to the ERE process, in the analyzed period, were: difficulties in adapting to emergency remote teaching, th e methodologies used by the professors were not entirely satisfactory, according to the students' evaluation; both teachers and students had difficulties using the Educ@ Platform. With regard to students' access to digital technologies, the lack of technol ogical devices and access to an internet network with a stable, reliable and unlimited connection were the main limitations reported. It was observed, as positive aspects, that ERE brought a new form of learning mediated by the use of digital technologies, namely, hybrid teaching and other formats mediated by digital technologies. In conclusion, therefore, it is necessary to invest in public policies aimed at including TDIC's in higher education, with the objective of reducing digital exclusion and teacher training, seeking digital literacy, training students to use digital technologies.